ANALISIS STRUKTUR ALUR DALAM NOVEL TAPAK JEJAK KARYA FIERSA BESARI - Oktaviani Oktaviani; Antonius Totok Priyadi; Agus Wartiningsih (Universitas Tanjungpura, 2021)
AbstrakThis research aims to find the structure of the plot in Fiersa Besari's novel Tapak Jejak. The theory used in this study is related to novels and plot structures. This study uses descriptive methods, qualitative research forms, and uses a structural approach. The source of the research data is the novel Tapak Jejak by Friersa Besari. The data collection technique in this research is documentary study technique. The data in this study are in the form of quotations of words, phrases, sentences that contain plot structures. Based on the results of data analysis, it can be concluded that: the plot structure in Friersa Besari's Tapak Jejak novel consists of 5 plot-building structures, namely 1) the opening of the story begins with the arrival of the main character, I and my friends in Ternate to start their adventure, 2) The appearance of conflict in this novel when Bung's character is confused about stepping or continuing his journey to where to go, 3) The increase in conflict starts with the Bung character who has finished setting foot in Manowari 4) The climax occurs during Bung's journey when he arrives at the Papua Nurgini Border who has no purpose to continue his journey again, 5) Conflict resolution when the Bung and his friend, Gio, sat in the long dock of a village in Maluku without giving anything up so that the character I remembered his mother. The results of this study can be implemented in Indonesian language learning in high school, especially in class XII even semester students. The author hopes that this research can be continued by further researchers to examine from other aspects, for example about the characters and characterizations in the novel Tapak Jejak by Friersa Besari.Keywords: Analysis, Novel, Plot Structure